Piotroski's F-Score in the Chinese A-Share market - Deng, Xiaoyu (Department of Finance and Tax, 2017)
This study examines whether Piotroski's (2000) F-Score strategy can successfully be applied to the Chinese A-Share market. The empirical evidence shows that in the Chinese A-Share market, the high F-Score portfolio significantly outperforms the low F-Score portfolio. Especially within a low BM firm sample, buying high F-Score firms and shorting low F-Score firms consistently, on average, generate 1.28% market adjusted profit per month. The results are robust for size partition. However, the benefits of Piotroski's F-Score strategy are concentrated in low liquidity and analyst following sample. Within the high BM firm sample, Piotroski's F-Score strategy cannot generate any significant return. The excess return of a low BM sample persists across time, as well as after controlling for size, book-to-market ratio, and market beta. In addition, if we measure risk in terms of beta and volatility, high F-Score firms are less risky than low F-Score firms. To conclude, the empirical evidence presented in this study suggests investors can use Piotroski's F-Score to identify mispriced stocks and earn abnormal returns in the Chinese A-share market, especially within a low BM firm sample.